2020
DOI: 10.52168/bjf.2020.32.01
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker-based variation in the growth hormone genes of Nile tilapia (Oreochromis niloticus)

Abstract: Polymorphisms in growth hormone genes have been found to cause variation in growth performance of fish. The objective of the study was to reveal variations in microsatellite loci located in the growth hormone genes of Nile tilapia (Oreochromis niloticus). Five microsatellite loci namely GH-MS01, IGFII, IGFII-MS01, IGFII-MS03, and STR were analyzed to assess the genetic variation in the growth hormone genes of four stocks of O. niloticus viz. FBG-Mini Hatchery, FM-Mini hatchery, Eon Aquaculture Ltd. and BFRI. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They produce more feces and waste. Ali et al [44], who worked on the effects of stocking density and ammonia excretion on Nile tilapia (O. niloticus), suggested raising the stocking density from 2.81 g fish/L to 14.07 g fish/L increased the ammonia level from 1.48 to 26.44 mg/L and yielded lower growth rates. Considering the increasing mass of fish per 1 liter of water, it can be concluded that as the fish grows, the ammonia content will also increase.…”
Section: Growth Performancementioning
confidence: 99%
“…They produce more feces and waste. Ali et al [44], who worked on the effects of stocking density and ammonia excretion on Nile tilapia (O. niloticus), suggested raising the stocking density from 2.81 g fish/L to 14.07 g fish/L increased the ammonia level from 1.48 to 26.44 mg/L and yielded lower growth rates. Considering the increasing mass of fish per 1 liter of water, it can be concluded that as the fish grows, the ammonia content will also increase.…”
Section: Growth Performancementioning
confidence: 99%